Green areas and health outcomes: a systematic review of the scientific literature (Italian Journal of Public Health, 2010)
Background: Growing medical evidence shows that access to the natural environment improves health andwellbeing, prevents disease and helps people recover from illness. Experiencing nature in the outdoors canhelp tackle obesity and coronary heart disease. Green areas exert their benefits on both physical and mentalhealth, promoting physical activity and strengthening the sense of community thus positively influencingsocial interaction. Urbanization poses problems through effects such as environmental pollution, accidents,heat island effects, climate change and a consequent demand for urban green areas.Material and methods: We performed literature searches of electronic journal databases for studies andreviews that focused on the relationship between green spaces and health. We looked at the effects onphysical health, mental health, social health, physical activity and well-being in its broadest sense and thenwe categorically organized our findings.Results: We found many contradictory and unexpected results. However, the reported findings were generallyconsistent and supported the current view that urban design and the availability of urban green spaces arekey elements of prosperity and individual/collective comfort, so as to influence both the perceived health andthe objective physical conditions in a measurable way. A weak relationship between physical activity levelsand green space availability is observed.Conclusions: The occasionally contradictory results that emerged in this study suggest that a population’sresponse to urban design interventions is often unpredictable. Further research is needed to quantify thestrength of relation between green spaces and urban health, but also to investigate the social and behaviouralaspects which are more difficult to measure and understand.
Keywords: green areas; health; well-being